Longitudinal study of MRI and functional outcome measures in facioscapulohumeral muscular dystrophy - Wang, Leo H. (BMC Musculoskelet Disord, 2021)
BACKGROUND: Facioscapulohumeral muscular dystrophy (FSHD) is a patchy and slowly progressive disease of skeletal muscle. For MRI to be a useful biomarker in an FSHD clinical trial, it should reliably detect changes over relatively short time-intervals (~ 1 year). We hypothesized that fatty change over the study course would be most likely in muscles already demonstrating disease progression, and that the degree of MRI burden would be correlated with function. METHODS: We studied 36 patients with FSHD and lower-extremity weakness at baseline. Thirty-two patients returned in our 12-month longitudinal observational study. We analyzed DIXON MRI images of 16 lower-extremity muscles in each patient and compared them to quantitative strength measurement and ambulatory functional outcome measures. RESULTS: There was a small shift to higher fat fractions in the summed muscle data for each patient, however individual muscles demonstrated much larger magnitudes of change. The greatest increase in fat fraction was observed in muscles having an intermediate fat replacement at baseline, with minimally (baseline fat fraction < 0.10) or severely (> 0.70) affected muscles less likely to progress. Functional outcome measures did not demonstrate marked change over the interval; however, overall MRI disease burden was correlated with functional outcome measures. Direct comparison of the tibialis anterior (TA) fat fraction and quantitative strength measurement showed a sigmoidal relationship, with steepest drop being when the muscle gets more than ~ 20% fatty replaced. CONCLUSIONS: Assessing MRI changes in 16 lower-extremity muscles across 1 year demonstrated that those muscles having an intermediate baseline fat fraction were more likely to progress. Ambulatory functional outcome measures are generally related to overall muscle MRI burden but remain unchanged in the short term. Quantitative strength measurement of the TA showed a steep loss of strength when more fatty infiltration is present suggesting that MRI may be preferable for following incremental change or modulation with drug therapy. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12891-021-04134-7.